ПРОБЛЕМЫ СОВЕРШЕНСТВОВАНИЯ КОНСТИТУЦИОННЫХ НОРМ - S. N. Sabikenov (Хабаршы. Заң сериясы, 2019)
Thus, the improvement of constitutional norms is a complex process that requires a special procedure for its implementation within the current Constitution.